Kandungan Logam Berat Timbal (Pb) Dan Kadmium (Cd) Pada Air, Sedimen Dan Organ Mangrove Di Perairan Tulehu - NUR ALIM NATSIR; YUSRIANTI HANIKE; MUHAMMAD RIJAL; SUHAEDIR BACHTIAR (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
Differences in the accumulation of heavy metals lead and cadmium in water, sediments and mangrove organs (roots, stems and leaves) found in the waters of Tulehu, Maluku Province. Samples were taken from three observation stations, namely stopping ships that are not operating (station 1), Tulehu harbor (station 2) and Control (station 3). Pb and Cd were analyzed using Atomic Absorption Spectrophotometer. Pb and Cd content in sediments is higher than in water. The highest Pb and Cd content is found in the stems then in the roots and leaves (stems> roots> leaves). Mangroves are one of the aquatic organisms that have the ability to absorb heavy metals in the aquatic environment. Key words: Mangrove, Pb, Cd, Heavy Metal